Voices of the field : DEIA champions in higher education - Cupid, Sherella; Tomlin, Antione D. (Research, theory, and practice within academic affairs., 2023)
"This book, tentatively titled, Voices of the Field: DEIA Champions in Higher Education, will explore the experiences and stories of Diversity, Equity, Inclusion, and Anti-racist (DEIA) champions and leaders within higher education. There is no doubt that in response to the United States' current racial climate that higher education institutions have DEIA at the forefront of their operations. Consequently, "as a Black academic or Blackademic educator and DEIA champion, I am not sure I always see institutions and organizations walking the walk and doing the work it takes to live up to those missions, visions, and strategic plans." (Tomlin, 2022, para. 1). From my experience, this is partly because institutions do not know how to support and encourage all higher education professionals, no matter working area, gender, or race to become more DEIA minded. So, this book will share stories of champions of DEIA along with how other higher education professionals jump in. Like some of my other projects, I approach this book from an asset-based approach where chapter authors are taking more of an anti-deficit approach. So, while each chapter author will explore the challenges and opportunities that come with being a DEIA champion within higher education, we will not focus entirely on what higher education institutions or doing wrong; rather, how the tools, tips, and strategies provided can help support current and potential champions of the work and field. One especially important contribution of this book is that authors come from many different spaces, departments, and divisions within higher education including: admissions, student life, curriculum and instruction, service learning, alumni relations, career services, intercultural affairs and many others. Additionally, chapter authors' demographics make up a wide range of ages, ethnicities, abilities, and expertise. Given the breadth of experiences, each chapter will provide poignant suggestions for DEIA champions across the nation as well as for institutions who are looking to better understand, advocate for, support their own DEIA champions. The work of DEI practitioners is a work that often goes unnoticed. The long days, nights, exhaustion, and lack of mental capacity due to constant going and potential burnout is the price practitioners pay to fight the fight of creating more equitable spaces. Griffin (2021) noted, "The DEI practitioner is becoming a household name in some industries-like education-an emerging staple." (p. xxv). I agree with Griffin; moreover, these household names are not getting the attention, respect, or resources they need to continue being successful in their roles. Additionally, I add anti-racist to DEI, as being anti-racist is an action. I argue it is the action that brings all the other pieces of the work together. Its the demonstration and active practice of fighting against racism that helps to shift and change a culture. This book will aid in showing all higher education professionals some approaches to being more effective DEIA champions while also taking action and moving more toward anti-racism as a mindset and way of being. Thus, Voices of the Field: DEIA Champions in Higher Education is positioned to be a must-read for all higher education professionals and institutions who are looking for strategies to support, promote, and encourage the growth and development of DEIA champions"--